2000
DOI: 10.1105/tpc.12.12.2311
|View full text |Cite
|
Sign up to set email alerts
|

A Segmental Gene Duplication Generated Differentially Expressed myb-Homologous Genes in Maize

Abstract: The myb -homologous p1 gene regulates the synthesis of flavonoid pigments in maize kernel pericarp and cob; these floral organs are greatly modified in size and shape compared with their counterparts in teosinte, the progenitor of maize. To elucidate the molecular evolution of the p1 gene in relation to its expression and possible functions in maize and teosinte, we have isolated a second maize gene ( p2 ) that is highly homologous with the p1 gene, and a related gene ( p2-t ) from Zea mays subsp parviglumis .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
120
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(128 citation statements)
references
References 52 publications
7
120
0
1
Order By: Relevance
“…Since most duplicated Arabidopsis regulatory genes show evidence of divergent expression (Duarte et al, 2006), many plant regulatory genes may experience subfunctionalization and/or neofunctionalization. A clear example is found in a P1-rr locus of maize (Zea mays), containing genes encoding two tandemly duplicated Myb-like transcriptional activators (Zhang et al, 2000). One MYB-like gene is expressed in the kernel pericarp, cob, tassel glumes, and silk and is responsible for pigmentation in these tissues, whereas the other gene functions in the developing anther and silk.…”
Section: Nic2-locus Erf Genes Function Differently In Nicotine Biosynmentioning
confidence: 99%
“…Since most duplicated Arabidopsis regulatory genes show evidence of divergent expression (Duarte et al, 2006), many plant regulatory genes may experience subfunctionalization and/or neofunctionalization. A clear example is found in a P1-rr locus of maize (Zea mays), containing genes encoding two tandemly duplicated Myb-like transcriptional activators (Zhang et al, 2000). One MYB-like gene is expressed in the kernel pericarp, cob, tassel glumes, and silk and is responsible for pigmentation in these tissues, whereas the other gene functions in the developing anther and silk.…”
Section: Nic2-locus Erf Genes Function Differently In Nicotine Biosynmentioning
confidence: 99%
“…These include the genetically unlinked ciszog1 and ciszog2 genes (Swigonova et al 2005), the tightly linked p1 and p2 genes (Zhang et al 2000), and the locally duplicated zein seed storage protein gene families that exhibit 98% identity (Song et al 2001). This study demonstrates that most NIPs are expressed and that individual members of many NIP families exhibit differential expression patterns.…”
Section: Discussionmentioning
confidence: 91%
“…Maysin accumulation is correlated with a phenotype termed silk browning, in which the cut ends of silks turn brown due to the oxidation of flavones (Byrne et al 1996;Lee et al 1998;McMullen et al 1998;Guo et al 2001;Rector et al 2003). Both p1 and p2 genes are expressed in maize silk (Zhang et al 2000), and both encode highly similar R2R3-Myb proteins with a similar potential to activate flavonoid biosynthesis in transgenic cell lines (P. . Previous studies have shown that a stock that contains both p1 and p2 genes has high maysin levels and strong silk browning.…”
Section: Resultsmentioning
confidence: 99%
“…Identification of deletions extending to the p2 gene and beyond: The p1 gene is linked with a second, highly similar gene termed p2; the p1 and p2 genes were proposed to have been generated by a segmental duplication followed by retroelement insertions to separate the two paralogs (Zhang et al 2000). If the p2 gene is located 59 of p1, then some of the SCT-generated deletions would be expected to have deletions that include p2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation